Assessment of executive functions in social phobia patients using the Wisconsin Card Sorting Test - (:unkn) unknown (Turkish Association of Nervous and Mental Health, 2009)
Objective: Problem solving and adjusting responses according to feedback are among the executive functions that may be impaired in social phobia patients. The objective of this study was to compare social phobia patients' Wisconsin Card Sorting Test scores with those of controls; thus, our aim was to examine executive functions in social phobia patients. Method: The study included 36 social phobia patients (16 female [44.4%] and 20 male [55.6%]) whose age, sex, and level of education were matched with those of a healthy control group. Participants were administered the Structured Clinical Interview for DSM-IV Axis I Disorders, Beck Depression Inventory, State-Trait Anxiety Inventory, Liebowitz Social Anxiety Scale along, and Wisconsin Card Sorting Test. Results: Patients with social phobia scored lower than the control group in terms of the total number of correct responses, number of categories completed, and percentage of conceptual level responses on the Wisconsin Card Sorting Test. The total number of errors and total non-perseverative errors were elevated in the patient group. No differences were observed in perseverative errors and set-maintenance between the patient and control groups. The number of correct responses and the percentage of conceptual level responses were negatively correlated with trait anxiety and social avoidance scores, whereas the number of errors was positively correlated with trait anxiety and social avoidance scores. Non-perseverative errors were positively correlated with stateanxiety, social fear, and social avoidance scores. Conclusion: Working memory in the social phobia patients was impaired, as compared to that of the healthy controls. High social anxiety scores had a negative impact on working memory.
Keywords: Executive functions; Social phobia; Wisconsin Card Sorting Test; Working memory